Oxford handbook of gastrointestinal nursing - Norton, Christine (Oxford handbooks in nursing., 2008)
The role of the gastrointestinal (GI) nurse has changed considerably over recent years. The development of endoscopic equipment has resulted in a demand for skilled nurses to perform procedures which, in the past, were carried out by doctors. In addition, nurses now commonly perform diagnostic tests and prescribe specific drugs in gastroenterology, and the widespread recognition of the need for psychosocial support for gastrointestinal patients, in areas such as Irritable BowelSyndrome (IBS), has seen a large increase in the number of GI nurse consultants, nurse specialists, and nurse practiti.- Resumé vydavatel